Applying the reasoned action approach to understanding health protection and health risk behaviors. (December 2017) - Conner, Mark; McEachan, Rosemary; Lawton, Rebecca; Gardner, Peter
Abstract: Rationale: The Reasoned Action Approach (RAA) developed out of the Theory of Reasoned Action and Theory of Planned Behavior but has not yet been widely applied to understanding health behaviors. The present research employed the RAA in a prospective design to test predictions of intention and action for groups of protection and risk behaviors separately in the same sample. Objective: To test the RAA for health protection and risk behaviors. Method: Measures of RAA components plus past behavior were taken in relation to eight protection and six risk behaviors in 385 adults. Self-reported behavior was assessed one month later. Results: Multi-level modelling showed instrumental attitude, experiential attitude, descriptive norms, capacity and past behavior were significant positive predictors of intentions to engage in protection or risk behaviors. Injunctive norms were only significant predictors of intention in protection behaviors. Autonomy was a significant positive predictor of intentions in protection behaviors and a negative predictor in risk behaviors (the latter relationship became non-significant when controlling for past behavior). Multi-level modelling showed that intention, capacity, and past behavior were significant positive predictors of action for both protection and risk behaviors. Experiential attitude and descriptive norm were additional significant positive predictors of risk behaviors. Conclusion: The RAA has utility in predicting both protection and risk health behaviors although the power of predictors may vary across these types of health behavior. Highlights: Reasoned Action Approach used to understand determinants of health behaviors. Examine intentions and action within individuals across health behaviors. Protection and risk behaviors have differing patterns of associations. Effects of controlling for past behavior explored. Within-subjects analyses in multi-level modelling aid understanding of determinants.